2018
DOI: 10.3390/ma11122538
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Liquid Crystal Display (LCD) Glass Waste as Supplementary Cementing Material (SCM) in Cement Mortars—Rationale Based on Hydration, Durability, and Pore Characteristics

Abstract: This paper assesses the feasibility of using liquid crystal display (LCD) waste glass as a supplementary cementing material in cement mortars. Two different sizes of LCD waste glass powder (LGP) particles were used (5 µm and 12 µm) with two substitution levels with cement in mortar (10% and 20%). The resulting mortars were evaluated for strength, hydration, porosity and durability through various experimental techniques. It was found that LGP particles lead to appreciable strength gain at all ages in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Finer WG powder (particles < 150 µm) shows better pozzolanic reactivity and filler effect, thus helping to produce more C-S-H products and a dense microstructure while developing more strength [79]. Kim et al [80] observed approximately 22% and 11% improvement in mortar compressive strength after replacing 10% cement with WG powder of 5 µm and 12 µm particle size, respectively. Omran and Tagnit-Hamou [81] reported a 35% improvement in the splitting tensile strength of concrete at the 28-day curing age when WG powder (particle size < 40 µm) was used to replace 20% cement.…”
Section: Mechanical Properties Of Concrete With Wg As Scmmentioning
confidence: 99%
“…Finer WG powder (particles < 150 µm) shows better pozzolanic reactivity and filler effect, thus helping to produce more C-S-H products and a dense microstructure while developing more strength [79]. Kim et al [80] observed approximately 22% and 11% improvement in mortar compressive strength after replacing 10% cement with WG powder of 5 µm and 12 µm particle size, respectively. Omran and Tagnit-Hamou [81] reported a 35% improvement in the splitting tensile strength of concrete at the 28-day curing age when WG powder (particle size < 40 µm) was used to replace 20% cement.…”
Section: Mechanical Properties Of Concrete With Wg As Scmmentioning
confidence: 99%
“…The LCD cement showed compressive strengths slightly smaller for the diameter of 12 μm; however, the compressive strengths were higher for cement with a 5 μm diameter (Figure 6). This phenomenon may be caused by the fact that the Si and Al ions in the LWGP reacted with the Ca ions, which were included in the pore solution, to form the C–S–H and C–A–H gels, thus producing a dense and more compact matrix [13].…”
Section: Resultsmentioning
confidence: 99%
“…OPC and two different types of LWGP were used as the primary binder in this experimental study. LWGP were prepared by grinding the LCD glass [13]. Table 1 shows the chemical properties of OPC and LWGP.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, the amount of nonrecyclable waste glass that went into landfills in the UK was about 1.65 million tons [115]. In 2015, Korea alone produced 40,000 tons of waste of Liquid Crystal Display (LCD) glass panels [116]. Although waste glass powder (WGP) can be categorized as a pozzolanic-cementitious material according to ASTM C618, the risk of alkali-silica reaction (ASR) has limited its use in cement-based materials [84,115,117].…”
Section: Scms From Solid Wastesmentioning
confidence: 99%